SOSIALISASI KEBIJAKAN PEMBATASAN USIA NIKAH BERDASARKAN UU NO. 16 TAHUN 2019 PADA SISWA MTSS MIFTAHUL ULUM PAKISAN - Amrotus Soviah (BAITUL JUHDI, 2025)
Based on the development of the times, such as the emergence of social issues, family matters, property, inheritance, and the increasingly complex knowledge regarding maternal and problem child health, the government has established regulations on the minimum age of marriage, namely Law No. 16 of 2019. This community service activity aims to increase knowledge about the age limits for marriage based on Law No. 16 of 2019. The implementation method of the activity was carried out through socialization of the definition of marriage, policies on age restrictions for marriage, and the goals and benefits of the age restriction policy for marriage. The participants of the activity were students and teachers of MtsS Miftahul Ulum Pakisan. The results of the community service activity showed an increase in understanding and changes in students' mindset about marriage and the age restriction for marriage. Some students realized that they have a role in the nation's development. Thus, students have the right to receive all rights granted by the state, including the right to welfare, education, health, obtaining identification, participating, being protected from violence, and obtaining identification. Students can grow and develop to their fullest potential and become excellent and competitive human resources for the progress of the nation. The policy of setting a minimum age for marriage provides benefits such as protection for children, opportunities for children to complete their education, reducing divorce rates, maintaining the reproductive health of girls, minimizing early marriage practices, accommodating values of gender equality, protecting children's psychological and reproductive well-being. This activity has proven successful in raising students' awareness about the policy of setting a minimum age for marriage.